PERNIKAHAN DINI DALAM PERSPEKTIF HUKUM KELUARGA ISLAM DAN HUKUM POSITIF INDONESIA: IMPLIKASI TERHADAP PEMENUHAN HAK DAN KEWAJIBAN SUAMI ISTRI(Studi Kasus di Desa Lubuk Betung) - Alwi Hidayat; Misbahuzzulam (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the practice of early marriage from the perspective of Islamic family law and Indonesian positive law, focusing on its implications for the fulfillment of the rights and obligations of husbands and wives. The main issue analyzed is the tension between the legality of marriage dispensations and the reality of young couples' unpreparedness to carry out household responsibilities. This study uses a normative juridical approach combined with an empirical approach through a review of legislation, Islamic family law literature, and field data from interviews in Lubuk Betung Village. The results show that early marriage leads to failure to fulfill physical and emotional needs, imbalance in husband-wife relations, weak family economic resilience, and increased conflict and divorce. These findings indicate that early marriage tends to fail to achieve the objectives of marriage in Islamic family law. Therefore, this study emphasizes the importance of the maqāṣid al-syarī‘ah approach, particularly ḥifẓ al-nafs and ḥifẓ al-nasl, as the basis for reconstructing marriage dispensation policies oriented towards the welfare of the family.